Citizen Participation In Local Governance: A Case Study Of Health And Sanitation Sectors In Gujranwala, Pakistan - Rafique, Zain (2017)
Contemporary development discourse confers a protuberant role to Citizen Participation (CP). To comply with this developmental demand, the Government of Pakistan introduced CP reforms and decentralization measures to use local governance system as a platform for localizing development and engaging local citizens. This thesis was designed to explore the level of Citizen Participation in the local governance system of Pakistan. The study explored both the subjective factors that include the role of stakeholders (local administrators, local political representatives, Civil Society Organizations and Citizens) and objective factors such as legal and administrative basis of CP.